THE ROLE OF HEMIS IN THE MANAGEMENT OF THE EDUCATIONAL SYSTEM OF UNIVERSITIES - Donabayev, Otabek (Journal of Contemporary World Studies, 2024)
The article analyzes the importance of digitalization and learning in the digital world in the HEMIS system of general secondary and higher education in our country, current activities and opportunities.